Generator of low pressure volume plasma with plasma electron source - Khomich, V.A.; Ryabtsev, A.V.; Nazarenko, V.G. (Вопросы атомной науки и техники, 2018)
In the current paper the results of a study of a volumetric high-current low-pressure discharge with a plasma electron source are presented. The source was made on the basis of a hollow cathode with a gas-magnetron ignition of the discharge and an auxiliary arc discharge for the cathode heating up to thermionic emission temperature. The gas-discharge plasma was generated at a working gas pressure 0.1...1 Pa and hade an electron concentration of 10¹⁰ ...(5×10¹¹) cm⁻³ in a volume of 0.1 m³. Also the volt-ampere characteristics, the ion current density distribution in the working volume are presented for different discharge conditions. The plasma generator may be used in the processes of ion-plasma technologies (oxidation, nitration in non-hydrogen media), as well as in energy-saving technologies of combined ion-plasma processing of structural materials. An improved electron plasma source with a hollow cathode will allow one to work in a wide range of discharge currents and also will be served for a large operating life of devices.